Neural circuits underlying context-dependent competition between defensive actions in Drosophila larvae - Lehman, Maxime; Barré, Chloé; Hasan, Md Amit; Flament, Benjamin; Autran, Sandra; Dhiman, Neena; Soba, Peter; Masson, Jean Baptiste; Jovanic, Tihana (Nature Communications, 2025)
To ensure their survival, animals must be able to respond adaptively to threats within their environment. However, the precise neural circuit mechanisms that underlie flexible defensive behaviors remain poorly understood. Using neuronal manipulations, machine learning-based behavioral detection, electron microscopy (EM) connectomics and calcium imaging in Drosophila larvae, we map second-order interneurons that are differentially involved in the competition between defensive actions in response to competing aversive cues. We find that mechanosensory stimulation inhibits escape behaviors in favor of startle behaviors by influencing the activity of escape-promoting second-order interneurons. Stronger activation of those neurons inhibits startle-like behaviors. This suggests that competition between startle and escape behaviors occurs at the level of second-order interneurons. Finally, we identify a pair of descending neurons that promote startle behaviors and could modulate the escape sequence. Taken together, these results characterize the pathways involved in startle and escape competition, which is modulated by the sensory context.
CRIS-Team Scopus Importer:2025-02-17